A Geomorphic Classification of Gunung Basor Reserve, Jeli, Kelantan. - Siti Nor Azlina Mohd Nordin (2013)
Gunung Basor Forest Reserve in Jeli, Kelantan is the forest reserve that still keeps most of their wilderness criteria and ecosystems. This research and study gathers a valid method for the geomorphological classification of GBFR, as well as its development with Geographic Information System (GIS). Since landform on earth surface are expensive to map and monitor, GIS offers detecting, analyzing, and time cost effective way to identified and classified the landform. The identification and classification of geomorphic process is based on particular references from Geomorphic Classification System of USDA Forest Service. With the aid of GIS analysis and satellite imaginary, the geomorphological map of GBFR is produced with the validation of the aerial photograph of the study area. The distribution of the geomorphic process and landform have been differentiated and identified with particular references to Geomorphic Classification System develop by Haskins et al., (1998). There are five geomorphic process and landform identify in GBFR. Thus a finding shows that, there is clear dominance of batholiths landform in GBFR. There are also other tectonic process identified; faulting and fault scarp. Floodplain and fluvial erosion also covered in the GBFR. The geomorphic map produced in this study will aid in the future research in the study area and act as preliminary study of ecosystem and ecology approach to manage this forest reserve. Likewise, in the last years the geomorphology begins to settle as the central point of many projects and implementation planning about forest management and land use with the aid of geomorphological map.